Understanding Financial Leverage: The Effect of Operating Leverage and Financial Leverage on EPS in Property and Real Estate Companies on the Indonesia Stock Exchange - Sapiri, Muhtar (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study aims to investigate the impact of operating leverage and financial leverage on earning per share (EPS) in the property and real estate sector of companies listed on the Indonesian Stock Exchange from 2017 to 2019. The results show that operating leverage has a positive and significant effect on EPS, while financial leverage has no significant effect on EPS. Simultaneously, both operating leverage and financial leverage have a positive and significant impact on EPS. The study suggests that investors should pay attention to the EPS of a company before making any investment decisions, as well as consider the use of debt on EPS to avoid potential losses. Additionally, the findings can assist companies in planning their operational funding through operating and financial leverage, and EPS can help maintain shareholders' trust and ensure their continued investment in the company. Thus, companies are advised to use debt wisely and consider EPS as a reference for investors when selecting company stocks.